Accessibility of Nonformal Education: Between Student Participation and Flexibility of Learning Time - Mintarsih Arbarini; Amin Yusuf; Decky Avrilianda (Journal of General Education and Humanities, 2026)
Nonformal Education offers distinct levels of accessibility compared to formal Education, heavily relying on student inclusion and flexible schedules to facilitate the learning process. However, the specific combined impact of active student involvement and schedule flexibility on overall educational accessibility remains underexplored. This study aims to examine how student involvement and time flexibility simultaneously influence the accessibility of nonformal Education. Using a quantitative research design, data from respondents were analyzed using a one-way ANOVA (F-test). The findings revealed a statistically significant combined effect of student involvement and time flexibility on nonformal education accessibility, Fcount = 11.023 > Ftable = 1.532, p < 0.05. It is concluded that nonformal Education becomes significantly more accessible when it prioritizes active student participation and flexible scheduling. These results imply that nonformal education providers should foster mutual agreements on the timing and location of learning to maximize student comfort, engagement, and overall educational accessibility.